Aksi Teror Dalam Perspektif Al-Qur’an: (Kajian Tematik Ibn Katsir Dalam Tafsirnya Al Qur’an Al Adzm) - Abdul Rouf (Sumbula: Jurnal Studi Keagamaan, Sosial dan Budaya, 2020)
This research is to describe and analyze Ibn Katsir's thoughts on terror in his tafsir book Al-Qur'an Al-'Adzim. The results of this study are expected to be used to add and deepen insights regarding terror in the perspective of the Al-Qur'an. This research is a library research with a qualitative approach. The material collected includes several theories, especially Ibn Katsir's commentary book "Al-Qur'an Al-'Adzim", other books and the opinions of experts that are related to the discussion of this research report. Then the data that was successfully collected and tested, then analyzed using descriptive analysis methods. The results showed: (1) The perpetrators of acts of terror during the time of the Prophet Muhammad were, among others, believers, because they defended their faith and honor when they were terrorized, Kafir Quraisy, Musyrik, Ahl Al-Kitab, Munafiq, Abu Lahab and his wife, Abu Jahal. (2) The law of terror can be divided into two, namely prohibited terror, because the law prohibits it and terror which is governed, the sharia governs it.